2009
DOI: 10.1038/emboj.2009.328
|View full text |Cite
|
Sign up to set email alerts
|

MOM1 and Pol-IV/V interactions regulate the intensity and specificity of transcriptional gene silencing

Abstract: It is commonly observed that onset or release of transcriptional gene silencing (TGS) correlates with alteration of repressive epigenetic marks. The TGS regulator MOM1 in Arabidopsis is exceptional since it regulates transcription in intermediate heterochromatin with only minor changes in epigenetic marks. We have isolated an enhancer of the mom1 mutation that points towards regulatory interplay between MOM1 and RNA polymerase-V (Pol-V). Pol-V transcribes heterochromatic loci, which seems to be required for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(119 citation statements)
references
References 61 publications
7
112
0
Order By: Relevance
“…S4A). Overexpressed TEs in all three genotypes profiled by RNA-seq are predominantly located in the pericentromeric heterochromatin and belong to diverse families, consistent with previous reports (18,26) (Fig. S4 B and C).…”
Section: Atmorc6 and Mom1 Act Synergistically To Silence A Common Set Ofsupporting
confidence: 77%
See 3 more Smart Citations
“…S4A). Overexpressed TEs in all three genotypes profiled by RNA-seq are predominantly located in the pericentromeric heterochromatin and belong to diverse families, consistent with previous reports (18,26) (Fig. S4 B and C).…”
Section: Atmorc6 and Mom1 Act Synergistically To Silence A Common Set Ofsupporting
confidence: 77%
“…Previous studies showed that DNA methylation in mom1 mutants was similar to the wild-type level (17)(18)(19)21). This observation was recently confirmed by genome-wide bisulfite-sequencing (BS-seq) analyses (43).…”
Section: Atmorc6 and Mom1 Act Synergistically To Silence A Common Set Ofsupporting
confidence: 58%
See 2 more Smart Citations
“…Tiling array hybridization data were processed with the R statistical software (www.r-project.org) and BioConductor (www.bioconductor.org) applying the chip definition file (CDF), kindly provided by Naouar et al (2009), as previously described (Yokthongwattana et al, 2010).…”
Section: Analysis Of Gene Expressionmentioning
confidence: 99%